Association of particulate matter air pollution with leukocyte mitochondrial DNA copy number - Xinmei Wang; Jaime E. Hart; Qisijing Liu; Shaowei Wu; Hongmei Nan; Francine Laden (Environment International, 2020)
Background: Ambient particulate matter (PM) has been associated with mitochondrial damage and dysfunction caused by excessive oxidative stress, but the associations between long-term PM exposure and leukocyte mitochondrial DNA copy number (mtDNAcn), a biomarker of mitochondrial dysfunction due to oxidative stress, are less studied. Objectives: To investigate the associations between short-, intermediate- and long-term exposure (1-, 3- and 12-months) to different size fractions of PM (PM2.5, PM2.5-10 and PM10) and leukocyte mtDNAcn in a cross-sectional study. Methods: The associations between each of the PM exposure metrics with z scores of log-transformed mtDNAcn were examined using generalized linear regression models in 2758 female participants from the Nurses’ Health Study (NHS). Monthly exposures to PM were estimated from spatio-temporal prediction models matched to each participants’ address history. Potential effect modification by selected covariates was examined using multiplicative interaction terms and subgroup analyses. Results: In single-size fraction models, increases in all size fractions of PM were associated with decreases in mtDNAcn, although only models with longer averages of PM2.5 reached statistical significance. For example, an interquartile range (IQR) increase in 12-month average ambient PM2.5 (5.5 μg/m3) was associated with a 0.07 [95% confidence interval (95% CI): −0.13, −0.01; p-value = 0.02] decrease in mtDNAcn z score in both basic- and multivariable-adjusted models. Associations for PM2.5 were stronger after controlling for PM2.5-10 in two size-fraction models. Conclusions: Our study suggests that long-term exposure to ambient PM2.5 is associated with decreased mtDNAcn in healthy women.